2020
DOI: 10.1128/aac.02320-19
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime-Avibactam To Treat Life-Threatening Infections by Carbapenem-Resistant Pathogens in Critically Ill Mechanically Ventilated Patients

Abstract: Data on the effectiveness of ceftazidime-avibactam (CAZ-AVI) in critically ill, mechanically ventilated patients are limited. The present retrospective observational cohort study, which was conducted in two general intensive care units (ICUs) in central Greece, compared critically ill, mechanically ventilated patients suffering from carbapenem-resistant Enterobacteriaceae (CRE) infections receiving CAZ-AVI to patients who received appropriate available antibiotic therapy. Clinical and microbiological outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 26 publications
(35 reference statements)
2
41
1
3
Order By: Relevance
“…Consistent with previous reports [17,32], we were unable to detect adverse drug events related to ceftazidime-avibactam treatment, even when the drug was administered for a relatively prolonged period of time (median of 13 days (range 2-49 days)). However, due to the retrospective nature of our data we are limited to that information reported in the medical records.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous reports [17,32], we were unable to detect adverse drug events related to ceftazidime-avibactam treatment, even when the drug was administered for a relatively prolonged period of time (median of 13 days (range 2-49 days)). However, due to the retrospective nature of our data we are limited to that information reported in the medical records.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical cure at the test-of-cure visit was achieved by 68.8% of CAZ-AVI recipients in the clinically modi ed intent-to-treat population, and by 77.4% in the clinically evaluable population from data of phase III REPROVE trial (40). Recently, a study from Tsolaki et al showed that patients with CAZ-AVI had improved clinical cure rates (80.5%), microbiological eradication (94.3%) and 28-day survival rates (85.4%) than those with other available antibiotic agents (41). It is hypothesized that these variations are primarily due to all the patients in the present study having HAP/VAP, higher Charlson's comorbidity scores, more complicated risk factors for multisite infections and a greater risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, this PD target is significantly lower than the suggested ß-Lactam targets of 100% fT> MIC or 100% fT> MICx4 in critically ill patients. Nevertheless, this standard dosage regimen of ceftazidime-avibactam has resulted in superior clinical success and survival than other treatment regimens to treat life-threatening infections by carbapenemresistant pathogens (42,43).…”
Section: Ceftzidime-avibactammentioning
confidence: 99%